CLINICAL AND ECONOMIC EVALUATION OF INHALATION ANESTHETICS USE - R. R. Gubaydullin; D. Yu. Belousov; A. E. Cheberda (Вестник анестезиологии и реаниматологии)
Sevoflurane is one of the widely used inhalation anesthetics as well as desflurane, which started to be used in Russia in 2012. These drugs possess similar properties; however, desflurane provides faster restoration of cognitive functions and reduces the time to extubation. This study was aimed to investigate the impact of properties of these medications on pharmacoeconomic parameters. The objective is to evaluate pharmacoeconomic parameters of anesthesia with desflurane and sevoflurane in a medical unit, investigating their impact on the performance of surgical teams and opportunity to introduce Fast-track surgery in the Russian Federation. Methods. For the purpose of cost-effectiveness analysis (CEA), the time period for simulation of the compared regimens made 1 year. And the time period for budget impact analysis (BIA) and additional analysis of Fast-Track surgery made 3 years. Results of randomized clinical trials were used as a source of data on safety and clinical efficiency. The simulated groups (100 patients each) were formed for the purpose of analysis. The decision tree was used, including all direct medical costs of anesthesia, and surgery in general (dextral hemicolectomy was analyzed). The number of surgeries performed in case of the maximum load in a medical unit was used as an efficiency criterion for CEA, and the full scope of costs for additional surgeries was also included. Result: Desflurane demonstrated maximum absolute efficiency, expressed as the number of surgeries in case of the maximum load in a medical unit, i.e. the best rate of cost-effectiveness (CER). CER for the regimen with desflurane made 63,251 RUR and CER for the one with sevoflurane made 63,841 RUR, The budget impact analysis showed that use of desflurane reduced the budget costs by 153,467 RUR during 3 years (provided that there are 247 surgeries per year and 3 surgeries per day). Sensitivity analysis confirmed the invariance of the obtained results. Analysis of potential introduction of Fast-Track surgeries showed that its use was associated with reduction of budget costs by 8,013,182 RUR. Conclusion: Use of anesthesia with desflurane resulted in higher effectiveness and was the most cost-effective providing reduction of budget costs.